Focus on Hyperparasites: Biotic and Abiotic Traits Affecting the Prevalence of Parasitic Microfungi on Bat Ectoparasites - Péter, Áron; Mihalca, Andrei Daniel; Haelewaters, Danny; Sándor, Attila D. (Frontiers in Ecology and Evolution, 2022)
The tritrophic association of bats, bat flies, and Laboulbeniales microfungi is a remarkably understudied system that yet may reveal patterns applicable to community ecology theory of (hyper)parasites. Laboulbeniales are biotrophic microfungi, exclusively associated with arthropods, with several species that are specialized on bat flies, which themselves are permanent ectoparasites of bats. Several hypotheses were tested on biotic and abiotic traits that may influence presence and prevalence of hyperparasitic Laboulbeniales fungi on bat flies, based on southeastern European data. We found a wide distribution of fungal infection on bat flies, with underground-dwelling bats hosting more infected flies compared to crevice-dwelling species. Bat host behavior, sociality, roost selection (underground versus crevice), bat fly sex, and season all have significant effects on the prevalence of fungal infection. Laboulbeniales infections are more common on bat flies that are infecting bat species with dense and long-lasting colonies (Miniopterus schreibersii, Myotis myotis, My. blythii), which roost primarily in underground sites. Inside these sites, elevated temperature and humidity may enhance the development and transmission of Laboulbeniales fungi. Sexual differences in bat hosts’ behavior also have an effect on fungal infection risk, with densely roosting female bat hosts harboring more Laboulbeniales-infected bat flies.